THE DEVELOPMENT OF THE FOREIGN LANGUAGE TEACHER’S CREATIVE ABILITIES IN THE CONDITIONS OF CONTINUOUS VOCATIONAL EDUCATION - Uglov , Vladimir; Varlamova, Irina; Chistyakov, Alexander; Vasilenko, Pavel; Semaeva, Olga; Shumakova, Serafima; Khmeleva, Alesya (Revista Inclusiones, 2020)
The phenomenon of creativity is seen by different scientists as an activity, as an aspect of personal development, as a form of intellectual activity, as a synthesis of a personality’s individual psychological peculiarities and new quality conditions. The characteristics of creativity include novelty, high quality of the product, freedom of thought, originality and anomaly (illogicalness). In our research, we will view creativity as an aspect of personal development. In the most general way, creative abilities in the modern psychological and pedagogical sciences are identical to the notion of creativity, which is seen as a general, diagnostically verified capacity for creativity. The most accepted definition of this phenomenon is an individual’s ability to generate extraordinary ideas, find original solutions, and go off the bitten track. The pedagogue’s professional creativity is the ability to generate many diverse original ideas in non-prescribed circumstances of the pedagogue’s activity. It is a dynamic component of the pedagogue’s professionally significant qualities which includes the intellectual, individual, social and emotional components, whose composite development influences the effectiveness of the pedagogue’s performance and its development. This is the pedagogue’s professional creativity which is that very form of realized creative abilities which directly influences the educational process and which represents the necessary level of their development for an effective realization of modern educational technologies.